Making Dry Herbarium Preservation To Support Biodiversity Lessons In Schools - Nurul Hidayah Nasution; Irda Wahidah Nasution (International Journal of Community Service Implementation, 2024)
Herbariums are plant specimens that have been preserved and can be used as learning media. There are two types of herbarium, namely dry herbarium and wet herbarium. The most common type of dry herbarium used as a learning medium. Dried herbaria are plant parts that have been dried and arranged on paper and then accompanied by information regarding the specimen. Making herbarium preserves is one of the main sources for studying biodiversity in the surrounding environment. So that students can feel ownership, understand and protect the biodiversity in their area, learning about biodiversity conservation will not be enough just to study conservation theories in the classroom. Students need to be invited to get to know biodiversity in its natural habitat, therefore teachers need to have knowledge and skills on how to collect and preserve organisms so they can be used as learning material in the laboratory. The method used in this service activity is training and performance in the form of practice. Training materials for the process of making dry herbarium include collection techniques, drying/pressing, applying sublimate, gluing to herbarium paper and labeling, equating it with living plants that are known by name in the school environment. The activity of delivering material for making a herbarium was carried out classically, all participants (students) followed the material presented by means of lectures, discussions and questions and answers. After completing the material delivery activity, a practical demonstration of making a dry herbarium was carried out using plants found in the school environment. For practical activities, participants were divided into groups of 3-5 members each. The students continued with the practice of making herbarium with the activity of gluing dried specimens to herbarium paper and labeling them. When gluing specimens, assistance is carried out intensively by researchers to provide guidance to students so that the process is carried out properly and correctly. Students gain a lot of knowledge about the principles of gluing specimens whose patterns are adapted to each student's creativity. Each group presented their own herbarium in front of the class which the other groups responded to.